Group-Based Parent Education Intervention for Nonresident Fathers. (November 2021) - Perry, Armon R.; Langley, Cheri
Research indicates that children with involved fathers fare better than children with disengaged fathers. In response, 4 Your Child provides fatherhood-specific parent education and solution-focused case management services aimed at helping nonresident fathers increase their capacity for taking more active roles in their children's lives. The purpose of this study was to present the results of preliminary analyses from a sample of 508 nonresident fathers enrolled in 4 Your Child. The results reveal high levels of participant satisfaction and statistically significant increases in parenting knowledge and conflict resolution skills for program participants from pre- to postintervention. Recommendations for future research and practice are also included.